Methodological Bases for Forecasting Passenger Flow on Regional Airlines - L.V, ERYGINA; E.V, BELYAKOVA; A.V, SELIVANOV; A.A, RYZHAYA (The journal of contemporary issues in business and government, 2021)
Air transport operation is a set of measures aimed at meeting the needs of air transportation. This complex includes measures to create demand for air transportation and satisfy it in order to generate profit. The successful functioning of the air traffic system in the region is largely determined by the accuracy and reliability of the forecast, which is especially important for socially significant routes. The forecast results are used at all stages of planning and operations, i.e. from the design of the air network to the formation of flight chains. This makes it possible, to plan economic indicators (such as incomes, including subsidies, and expenses, including financial payments), which directly affects the choice of tariff policy. The process of justifying all managerial decisions made both at the regional level and at the level of the airline should be based on the results of a predictive assessment of external and internal factors. Forecasting is a process that uses both past experience and current assumptions about the future to determine specific indicators in it. A set of methods is currently used to predict passenger traffic. The article analyzes the methods of forecasting passenger traffic used by various authors and proposes a methodological approach to forecasting passenger traffic on air routes in the northern territories of the Krasnoyarsk Territory. Within the framework of the proposed approach, a method for forecasting passenger traffic has been developed, a feature of which is to take into account such important factors such as the paying capacity of consumers, the purpose of their travel, and the availability of transport services by income level. The use of the methodological approach will make it possible to determine the predicted passenger traffic in order to achieve the target indicators of transport activity with minimal budgetary costs, as well as improve the quality and efficiency of management decisions made in the field of forecasting and logistics management of transportation processes.